Karakteristik Sensori Donat dengan Penambahan Emulsifier Mono-Diasilgliserol dari Fully Hydrogenated Palm Stearin - Ria Noviar Triana; Nuri Andarwulan; Arief R Affandi; Ria Choriatul Nur (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Emulsifiers are used in bakery industries to improve the quality and characteristics of products. Mono and diacylglycerol (MDAG) which can be produced from fully hydrogenated palm stearin (FHPS) is an emulsifier that can be applied in bakery products such as doughnut and bread. The objective of this study was to evaluate the effect of adding MDAG from FHPS as an emulsifier on dough characteristics, moisture content, extensibility and sensory quality of doughnut. Two concentrations of MDAG from FHPS in the formulation of doughnut were applied; i.e concentration 0.2% MDAG from FHPS and concentration 0.3% MDAG from FHPS. The results showed that the characteristics of dough with the emulsifier MDAG had smoth, not sticky, soft, easily molded and yellowish color. The dough became moist and air bubbles that form on the dough less. The moisture content of doughnut with the addition of MDAG ranged from 26.77% to 26.92%. MDAG from FHPS is capable to improve the extensibility and sensory quality of doughnut than that of the commercial emulsifier and control. Doughnut with the addition of 0.3% MDAG from FHPS as emulsifier had light brown skin color, rather glossy, uniform spread of skin color, and symmetrical spherical shape. The doughnut also had white crumb, good crumb matrix, fresh aroma, sweet avors, no wheat avor, smooth texture, not tough and easy to swallow.